THE IMPORTANCE OF PERSONALITY FACTOR FOR TEACHERS IN TEACHING PROCESS - Trikaloka H Putri (Educate, 2012)
Trikaloka H. Putri Universitas Pesantren Tinggi Darul Ulum princess.naura@gmail.com Abstract Many investigations have been conducted to find out the best formula for successful teaching and learning process. Many factors have been found related to the findings. Teacher is one of important factors that influence the successful teaching and learning process. Teacher is the one who knows well the condition of the students. Social and sociable seem to be important factors in teaching. The teacher who has the two factors will express friendly feelings for others. This teacher enjoyed their relationship with students and preferred nondirective to directive classroom procedures. This kind of teacher listens to the students, accepts students’ contribution and draws ideas from them. Keywords: personality factor, social, sociable Abstrak Banyak penelitian telah dilakukan untuk mengetahui formula terbaik untuk mendapatkan proses belajar mengajar yang sukses. Banyak faktor yang telah ditemukan. Guru merupakan salah satu faktor penting yang mempengaruhi kesuksesan proses belajar mengajar. Guru adalah orang yang tahu benar kondisi siswa. Sifat social and sociable menjadi faktor penting dalam mengajar. Guru yang memiliki dua faktor itu akan mengekspresikan perasaan ramah pada orang lain. Guru seperti ini menikmati hubungan mereka dengan siswa dan lebih menyukai prosedur kelas nondirective kepada para siswanya. Model guru ini mendengarkan para siswa, menerima masukan siswa dan menarik ide-ide dari mereka. Kata kunci: faktor kepribadian, sosial, dapat bersosialisasi